The macroeconomic impact of unconventional monetary policy shocks - Annette Meinusch; Peter Tillmann (Philipps-University Marburg, Faculty of Business Administration and Economics, 2014)
With the Federal Funds rate approaching the zero lower bound, the U.S. Federal Reserve adopted a range of unconventional monetary policy measures known as Quantitative Easing (QE). Quantifying the impact QE has on the real economy, however, is not straightforward as standard tools such as VAR models cannot easily be applied. In this paper we use the Qual VAR model (Dueker, 2005) to combine binary information about QE announcements with an otherwise standard monetary policy VAR. The model filters an unobservable propensity to QE out of the observable data and delivers impulse responses to a QE shocks. In contrast to other empirical approaches, QE is endogenously depending on the business cycle, can easily be studied in terms of unexpected policy shocks and its dynamic effects can be compared to a conventional monetary easing. We show that QE shocks have a large impact on real and nominal interest rates and financial conditions and a smaller impact on real activity.
Keywords: E32; E44; E52; 330; Qual VAR; unconventional monetary policy; LASP; zero lower bound; quantitative easing